Persentase dan Tingkat Infestasi Nematoda Gastrointestinal (NGI) Pada Ternak Sapi Gayo Lues dan Aceh Timur Provinsi Aceh - Zulfikar Zulfikar; Sayed Umar; T. Reza Farasyi; Maruf Tafsin (Jurnal Serambi Engineering, 2018)
This study was conducted to determine the percentage and level of parasite infestation of gastrointestinal nematodes (NGI) in cattle based on different areas in Aceh Province. The samples in this study were cow feces taken each 3 (three) subdistricts in Gayo Lues District with 64 samples and East Aceh district with 93 samples. For sample examination and see infestation picture have been done with laboratory test by using Method of centrifuge and Mc method Master. For data analysis done with Prevalence test and formulation of Mc. Master. The results showed that based on percentage of gastrointestinal nematode attendance level in Gayo Lues District, there were 15 positive samples (23.44%), while in East Aceh of 93 samples examined there were 33 positive (35.48% ), seen a higherpercentage in East Aceh (0.05). Meanwhile, based on egg yield per gram of feces (TPGT) showed that Gayo Lues Regency is higher than East Aceh, where in Regency of  Gayo Lues from 15 positive number of eggs there were 20,661 grains (1377 grains / head), while in East Aceh from 33 positive , the number of eggs is only 23,595 grains (715 eggs / head), seen from TPGT result shows there is real difference (p 0,05).